Investigating Female Middle Manager Career Progress In Malaysia Public Listed Companies - Jamir Singh, Malvinder Kaur (2020)
The relative failure of women to move into top rank positions in management is an essential topic of concern. Women participation in the work force is not only a women issue but is also about sustainable growth of organisations and the economy. By studying and understanding existing barriers, women in middle management positions can be assisted to obtain top management positions. Thus, the present study has examined to what extent do independent variables such as organisational practices, motherhood and work-life conflict respectively, contribute to women career progression.